Palaeoenvironmental significance of a late Miocene benthic foraminifera fauna from Apostoli Formation, Central West Crete, Greece - DRINIA, H. (Bulletin of the Geological Society of Greece, 2018)
The palaeoenvironmental and palaeoecological reconstruction of the Apostoli Basin (Crete, Rethymnon Region) during early Late Miocene by means of benthic foraminifers is given. Biologically important factors, such as oxygen and nutrient content of sea-water, played a great role in the evolution of the palaeoecosystem. A gradual deepening took place during the deposition of the Apostoli Formation. The sediments of the lower part of the formation document a shallow-marine environment with vegetation in the neighborhood. In the middle part of the formation sediments are characterized by intermediate oxygenated conditions, whereas the upper part of it is characterized by the establishment of a restricted envrironment, where organic matter accumulates and infaunal opportunistic species capable of surviving in stressed conditions dominate, being favoured by abundant nutrients.